Pelaksanaan Perjanjian Antara PT. Garda Lintas Sarana Dengan Pengguna Jasa: (Studi di Garda Express Mataram) - DIMAS WAHYU PUTRA; H. Zaenal Arifin Dilaga; Fatria Hikmatiar Al Qindy (Private Law, 2023)
This study aims to explain the implementation of the agreement between Garda Express Mataram and service users based on contract law and find out the responsibility of Garda Express Mataram for the loss of goods sent by service users. This study uses a type of normative and empirical research using the statutory approach (Statute Approach), conceptual approach (Conceptual Approach), and sociological approach (Sociological Approach). The data collection technique used was field research and library research. The results of research in the field indicate that there are legal issues that occur in the process of delivering goods to service users or consumers, while the company's efforts to resolve them are replacing lost consumer goods by replacing a maximum of 10 (ten) times the cost of shipping goods or the price of goods taken from the lowest value if the loss is caused by the negligence of the officer.